Drying and storage studies in nutmeg (Myristica ragans Houtt) - S. Naveen Kumar (Department of Processing Technology, College of Horticulture, 2013)
Nutmeg (Myristica fragrans Houtt.) known in Malayalam as ‘Jathikka’ is one of the most important spices grown in Kerala. Although nutmeg is available for harvest throughout the year, its peak harvest season lies in the months of June to August during which the soil microorganisms are also active and as a result, nutmeg collected in that season will be with high initial microbial load. Therefore an attempt has been made to reduce the initial microbial load and also to develop a suitable drying and storage technique for nutmeg. In both harvested and fallen nutmeg, washing with 1000 ppm luke warm alum water was found effective in reducing high initial microbial load to a low level. Mechanical drying of nutmeg in a cabinet drier was found to be the best method of drying as it was quick and yielded the product with minimum loss of colour, oil and oleoresin. Total sensory score was also highest in cabinet dried samples. Among the packaging materials tried aluminium foil laminated pouches were better than other packaging materials as the products stored in aluminium laminated pouches showed highest oil and oleoresin contents and at the same time least microbial population even after six months of storage. Highest total sensory score was also recorded in the mace samples stored in aluminium laminated pouches. The techniques thus developed could be effectively used in reducing the high initial microbial load and also to store the materials for a longer period of time without much spoilage and quality deterioration.